Jaccoud arthropathy in systemic lupus erythematosus: clinical and serological findings - Skare,Thelma L. (2012)
OBJECTIVE: To study the prevalence of Jaccoud arthropathy (JA) in a sample of local systemic lupus erythematosus (SLE) patients and its clinical and serological associations. METHODS: 308 SLE patients from a single university center for the last two years were interviewed and examined. The presence of JA was searched for according to the JA index. After this, charts were reviewed for clinical and serological profile. RESULTS: The studied sample was composed by 94.5% females and 5.5% males with mean age of 38.08 ± 12.04 years and mean disease duration of 29.68 ± 11.63 years. A JA prevalence of 6.1% was found in this sample. There was a positive association of JA presence with arthritis complaints (p = 0.001) and a negative association with renal involvement (p = 0.028). Patients with JA had higher positivity for anti-dsDNA (p = 0.022). CONCLUSION: Despite the positive association of JA with arthritis and anti-dsDNA, there was a negative association with nephritis. This could suggest that JA patients belong with a SLE subset with a better prognosis.